Evaluating the Potential of Immersive Virtual Reality-Based Serious Games Interventions for Autism: A Pocket Guide Evaluation Framework - Sara Peretti; Maria Chiara Pino; Federica Caruso; Tania Di Mascio (MDPI AG, 2024)
To date, the primary challenge in the field of information and communication technologies-mediated rehabilitative interventions for autism is the lack of evidence regarding efficacy and effectiveness. Although such interventions, particularly those realised with Immersive Virtual Reality-based Serious Games, show promise, clinicians are hesitant to adopt them due to minimal evidence supporting their efficiency and effectiveness. Efficacy refers to whether an intervention produces the expected result under ideal circumstances, while effectiveness measures the degree of beneficial effect in real-world clinical settings. The absence of efficacy and effectiveness evidence undermines the reliability and generalisability of such interventions, which are crucial for real-life settings, making accurate evaluation pivotal. Evaluating the efficacy and effectiveness of these interventions poses a significant challenge due to the absence of evaluation guidelines. A previous study systematically reviewed the evaluation of Immersive Virtual Reality-based Serious Games for autism, revealing incomplete or methodologically problematic evaluation processes. This evidence underpinned the aim of the present study: to propose an Evaluation Framework encompassing all necessary methodological criteria for evaluating the efficacy and effectiveness of such interventions. Disseminating this Evaluation Framework as a pocket guide could facilitate the development of reliable future studies, thereby advancing evidence-based interventions to improve the quality of life for individuals with autism.